A Poetics of Art Criticism : The Case of Baudelaire - Raser, Timothy Bell (Book collections on Project MUSE., 1989)
Raser questions criticism's predilection for a scientific discourse, arguing that aesthetic categories are better indicators of a text's literary qualities. Although aesthetics has claimed subjective pleasure as its sole criterion since the time of Kant, aesthetic judgments tend always to ground themselves in logic or reference. In art criticism, description serves as this ground and is no more productive than in Baudelaire's art criticism, where it leads to poetry.